The Leadership Style of Female Heads of Household in Coffee Farming Amidst the Masculinity of Coffee Plantations - Wahyudi, Fidela Dzatadini; Ibrahim, Jabal Tarik; Soedarwo, Vina Salviana Darvina (Technium Social Sciences Journal, 2025)
The limitations of space and opportunities for women in patriarchal cultures hinder them from demonstrating their leadership abilities. Women are often perceived as weak in terms of physical, psychological, and intellectual capabilities, leading patriarchal societies to predominantly entrust leadership roles to men. This study conducts an in-depth analysis of female leadership styles in coffee plantations, historically male-dominated, when women are afforded the opportunity to lead, particularly after separation from their husbands, whether through divorce or widowhood, thereby becoming female heads of households. The study employs a phenomenological method and Beauvoir’s concept of transcendence. Findings reveal that male leadership tends to segregate tasks based on gender, distinguishing between those suitable for men and women, whereas female leadership emphasizes delegation, empathy, and non-discriminatory task assignment, regardless of gender.